Managerial accounting - Anderson, Henry R.; Caldwell, James C.; Mills, Sherry K.; Needles, Belverd E. (Houghton Mifflin, 1994)
This book is about: Fundamentals of management accounting; Planning and control for managers; Accounting for management decision making; Management accounting; ...